The Nagorno-Karabakh Conflict: The principle of sovereignty and the right to self-determination. - CRIŞAN, Alexandru-Vlad (International Journal on Humanistic Ideology)
This paper tries to shed some light on the aspects in regard to the principle of sovereignty and the right to self-determination as decisive elements in the course of the Nagorno-Karabakh war. Defining sovereignty and the right to self-determination as well as linking them to the conflict in Transcaucasia is the first part of this paper. Likewise, the reactions of the Azeri government and civil society are also analysed, as well as the factors which influenced the outcome of the conflict. Simultaneously, we shall analyse how the structure of the political power of the two states was formed as a result of the conflict in Mountainous Karabakh. Last but not least, the relation between the central leadership of the USSR with Azerbaijan and Armenia will be analyzed.